Estratégias de ensino na educação profissional e tecnológica: o uso da cultura maker no programa Educa+ Amazonas - Maia, Adriana Gama do Nascimento (2023)
In the modality of Vocational Education Training (VET), teaching strategies involve methodologies, techniques and active practices planned and implemented in formal and informal learning environments in order to access, produce and express the student's knowledge. Considering that this study focuses on teaching resources and methodological proposals for the comprehensive transformation of the student, the overall objective of this research was to enhance the use of the maker culture in vocational and technological education through the Educa+ Amazonas Program, in order to make classes more practical, dynamic and interactive for the absorption of the content covered. Terms such as experimentation, curiosity, stimuli and research are fundamental for the development of critical thinking in students, who learn through their own experiences. The theoretical contribution is anchored in the theory of experimentation and research of DEWEY (2001), in the active methodologies present in the assumptions of MORAN (2019) and the formative process focused on the work of SAVIANI (1995). For this, it was chosen the case study in research of applied nature, with quali-quantitative approach due to the complementation given that enriched the analysis and final discussions. The data collection was done through semi-structured questionnaires applied to teachers and students of the technical courses of Computer Network and Electronics of the Benjamin Constant unit (IBC) of the Technological Education Center of Amazonas (Cetam). The results presented by the research showed the need for a manual with teaching strategies for the use of maker culture, culminating in the preparation of a guide as an Educational Product of the Postgraduate Programme in Vocational Education and Training entitled "Maker Culture: a teaching strategy in strengthening the teaching work in VET". Thus, the educational use of maker culture can become an important methodology in human and integral training of students.